2014
DOI: 10.4038/cjsbs.v43i1.7283
|View full text |Cite
|
Sign up to set email alerts
|

Bird Diversity of Dekinda Forest Reserve, Balana, Sri Lanka: Implications for Conservation

Abstract: Dekinda Forest Reserve, located close to the historic town of Balana, Sri Lanka (7 o 16' N, 80 o 29' E, 525-585 m above sea level) consists of rainforest plant species spanning an area of about 40 ha. The forest has been maintained since the colonial times as a watershed reserve for nearby plantations, most of which comprised tea and paddy. The objective of the present study was to measure the avifaunal diversity in Dekinda Forest Reserve, as an indicator of its overall biodiversity, and compare it with those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…A study done in Ritigala Strict Natural Reserve in the northcentral dry zone has recorded 97 bird species out of which five endemic species (which means low endemism) (DWC, 2008). A more recent study conducted in Dekinda Forest, which is a hill rain forest enclosed by a municipal area in Balana has recorded 56 bird species with 34% of endemism (Wijesundara and Wijesundara, 2014). The percentage endemism in Dekinda forest is somewhat closer to the present study.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…A study done in Ritigala Strict Natural Reserve in the northcentral dry zone has recorded 97 bird species out of which five endemic species (which means low endemism) (DWC, 2008). A more recent study conducted in Dekinda Forest, which is a hill rain forest enclosed by a municipal area in Balana has recorded 56 bird species with 34% of endemism (Wijesundara and Wijesundara, 2014). The percentage endemism in Dekinda forest is somewhat closer to the present study.…”
Section: Discussionsupporting
confidence: 74%
“…For all other contacts, the radial distance was estimated to the nearest meter (Wijesundara and Wijesundara, 2014). For a group of birds, the geometric centre was considered to estimate the distance (Ralph and Scott, 1981;Wijesundara and de Silva, 2005).…”
Section: Distance Samplingmentioning
confidence: 99%
“…Despite the anthropophilic species such as brownheaded barbet, red-vented bulbul, and yellow-billed babbler [26,31] some forest loving birds such as Sri Lanka wood pigeon and emerald-collared parakeet [21] were observed to actively utilize resources available in these habitats. Although these observations are from our area of study, avian assemblages were typical to other neighborhood study systems available in literature [15,32,33]. The most important factors influencing avifaunal community structure were elevation, distance from the edge, and the canopy closure.…”
Section: Discussionmentioning
confidence: 82%
“…It was further observed that habitat edges are rich in raptors and other birds of prey (carnivore feeding guild). This may be due to an increased amount of microhabitats, visibility and prey (Kottawa-Arachchi et al 2012, Wijesundara andWijesundara 2014). A high abundance of granivores in edge habitats may be explained by the presence of grassy vegetation and domestic kitchen waste disposed of in home gardens, which attracts granivores.…”
Section: Discussionmentioning
confidence: 99%